Structural diversity of the complexes of monovalent metal d10 ions with macrocyclic aggregates of iso-tellurazole N-oxides. (25th July 2019) - Wang, Jin; Ho, Peter C.; Britten, James F.; Tomassetti, Valerie; Vargas-Baca, Ignacio
Abstract : Iso-tellurazole N -oxides yield a remarkable variety of structures with coinage-metal monocations. Abstract : The reactions of iso-tellurazole N -oxides with monocations of the coinage metals yielded a family of coordination complexes with a remarkable variety of compositions and structures. All new species were identified by single-crystal X-ray diffraction. In all cases, the macrocyclic aggregation of the organo-chalcogen heterocycles through Te⋯O chalcogen bonding interactions is preserved and the metal ions are coordinated by tellurium. Copper and gold formed complexes with the tetramers. The lighter element acquired a κ 4 Te, κ 1 O pentacoordinated square pyramidal structure with a triflate anion in the apical position. The preference of the heavier metal for a linear κ 1 Te, κ 1 Cl coordination geometry permitted the formation of a binuclear complex. Silver demonstrated a unique preference for coordinating to the hexamer; two distinct examples showed a structure with a pair of endocyclic κ 2 Te, κ 2 O metal ions bridged by two triflate anions; the other two chalcogen atoms are located at trans-annular positions and each coordinates a κ 1 Te, κ 1 O, κ 1 C silver ion, also bonded to an aromatic carbon and another triflate anion.